2016
DOI: 10.1016/j.dib.2016.02.085
|View full text |Cite
|
Sign up to set email alerts
|

mRNA and protein dataset of autophagy markers (LC3 and p62) in several cell lines

Abstract: We characterized the dynamics of autophagy in vitro using four different cell systems and analyzing markers widely used in this field, i.e. LC3 (microtubule-associated protein 1 light chain 3; protein recruited from the cytosol (LC3-I) to the autophagosomal membrane where it is lipidated (LC3-II)) and p62/SQSTM1 (adaptor protein that serves as a link between LC3 and ubiquitinated substrates), (Klionsky et al., 2016) [1]. Data provided include analyses of protein levels of LC3 and p62 by Western-blotting and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 4 publications
(6 reference statements)
2
26
0
1
Order By: Relevance
“…The ubiquitin‐binding protein p62 is involved in lysosome‐ or proteasome‐dependent protein degradation during autophagy flux activation. A defect in the autophagy process or blockage of lysosomal degradation indicated autophagy flux inhibition, and this was indicated by increased p62 protein expression . CG treatment for 12 hours resulted in a dose‐dependent increase in LC3‐II, indicating autophagosome formation, and decrease in p62, suggesting that lysosomal degradation occurred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitin‐binding protein p62 is involved in lysosome‐ or proteasome‐dependent protein degradation during autophagy flux activation. A defect in the autophagy process or blockage of lysosomal degradation indicated autophagy flux inhibition, and this was indicated by increased p62 protein expression . CG treatment for 12 hours resulted in a dose‐dependent increase in LC3‐II, indicating autophagosome formation, and decrease in p62, suggesting that lysosomal degradation occurred.…”
Section: Resultsmentioning
confidence: 99%
“…protein expression. 38 CG treatment for 12 hours resulted in a dosedependent increase in LC3-II, indicating autophagosome formation, and decrease in p62, suggesting that lysosomal degradation occurred.…”
Section: Cgs Led To Mitochondrial Dysfunction Via Antiapoptotic Bclmentioning
confidence: 99%
“…3ab) was essentially identical to the phenotype without the DM pre-treatment (Figure 2(a-b)), indicating the differentiation phenotype is independent of the proliferation phenotype. We also detected the expression levels of a caspase 3, a key apoptosis regulatory gene [94], and two key autophagy regulatory genes (LC3B and P62) [95] and found that FGF9 treatment did not alter their expression levels. This result indicated that FGF9 treatment did not alter C2C12 cell apoptosis and autophagy (Supplemental Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…E2 and PPT inhibited oleic acid-induced increase of p62/Sqstm1 mRNA. p62/Sqstm1 gene is a well-known autophagy marker (Gómez-Sánchez et al, 2016). Recent study showed that estrogen inhibits autophagy in endometrial cancer (Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%